Pedagogical Training as a Form of Preparing Future Educators of Pre-School Education Institutions to Implement Sustainable Development Ideas - Nataliia Myskova (Pedagogical Discourse, 2018)
On the basis of theoretical analysis, the types of psychological and socio-pedagogical training as forms of purposeful changes of human phenomena with the purpose of harmonization of professional and personal life have been singled out. The characteristic features and disadvantages of training as a form of organization of cognitive activity have been presented. The advantages of the training have been outlined: activity, combination of information and emotional attitude towards it, increase of level of motivation, group’s ability to collective thinking and decision making, practical examination and consolidation of the received knowledge. The emphasis is placed on the use of pedagogical training in preparing future educators of pre-school education institutions for the implementation of sustainable development ideas. In this context, the purpose and the tasks of the pedagogical training have been revealed, the conformity of principles of pedagogical training to the moral principles of psychological assistance have been indicated. The attributes of training have been singled out: training group; training circle; specially equipped premises and accessories for training (flipchart, markers, etc.); coach; group rules; atmosphere of interaction and communication; interactive teaching methods; structure of the training session; evaluation of the effectiveness of training. The methods and exercises of interactive training have been determined in the structure of educational pedagogical training.The taxonomy of B. Bloom’s cognitive goals has been given as a determining factor in the choice of the form of organization of training. The proposals on application of certain interactive training exercises according to each structural part of the training (introductory, main, final) have been put forward. The effectiveness of using moving exercises has been emphasized to switch the attention of the participants of the training. The necessity of using reflexive exercises has been mentioned and the attention has been paid to the differences between the analyses of the content from the analysis of the activity at the training. The dependence of the group’s performance on the personal and professional qualities of the trainer has been noted.